2011
DOI: 10.1073/pnas.1103165108
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule inhibitor binding to an N -acyl-homoserine lactone synthase

Abstract: Quorum sensing (QS) controls certain behaviors of bacteria in response to population density. In Gram-negative bacteria, QS is often mediated by N-acyl-L-homoserine lactones (acyl-HSLs). Because QS influences the virulence of many pathogenic bacteria, synthetic inhibitors of acyl-HSL synthases might be useful therapeutically for controlling pathogens. However, rational design of a potent QS antagonist has been thwarted by the lack of information concerning the binding interactions between acyl-HSL synthases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 23 publications
5
106
0
Order By: Relevance
“…74) Analog 79 showed 91% and 51% inhibitory activities at concentrations of 100 and 10 μM, respectively. A kinetic analysis indicated that 79 acted as a competitive inhibitor of TofI activity with a K i value of 4.8 μM.…”
Section: Inhibitors Of Acylhomoserine Lactone-synthesizing Enzymementioning
confidence: 99%
See 2 more Smart Citations
“…74) Analog 79 showed 91% and 51% inhibitory activities at concentrations of 100 and 10 μM, respectively. A kinetic analysis indicated that 79 acted as a competitive inhibitor of TofI activity with a K i value of 4.8 μM.…”
Section: Inhibitors Of Acylhomoserine Lactone-synthesizing Enzymementioning
confidence: 99%
“…This is the first study to show that flavonoids exuded from roots inhibited the function of strigolactones. Alpinumisoflavone (74), which was one of the most potent inhibitors of germ tube growth, did not inhibit the formation of new branching hyphae at 0.31, 0.63, or 1.25 μg/disk. Unexpectedly, high-order branches up to sixth or seventh hyphae were formed by the treatment with 74 at the three tested concentrations in the presence of 68.…”
Section: Production Of Strigolactones In Non-host Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, E9C-3oxoC6 was found to competitively inhibit C8HSL binding to the AHL receptor TofR. Structural studies of TofI in its apo form and in complex with J8-C8 revealed that the inhibitor binds in a pocket with high specificity for the octanoyl chain, suggesting that J8-C8 is a competitive inhibitor of the acyl-ACP carrier utilized for C8HSL synthesis, and thus it has been postulated that modulation of acyl chain length in J8-C8 mimics may be a means by which to rationally design enzyme-specific LuxI family inhibitors (119). Separately, holo-ACP, the SAM analogues S-adenosylhomocysteine, S-adenosylcysteine, and sinefungin, the reaction product methylthioadenosine (MTA), and the possible reaction intermediate butyryl-SAM were found to inhibit C4HSL production by RhlI in vitro (27), demonstrating that LuxI-type synthase activity could also potentially be inhibited by end products, reaction intermediates, and/or substrate analogues.…”
Section: Inhibition Of Ahl Productionmentioning
confidence: 99%
“…A screen of 55 "hits" from a previous quorum-sensing screen in P. aeruginosa (118) yielded the identification of two strong inhibitors of QS in B. glumae (119). Although both compounds inhibited C8HSL production, they were found to do so in different ways; whereas both E9C-3oxoC6 and J8-C8 (Table 3) suppressed toxoflavin production in WT cells, only E9C-3oxo-C6 had an effect in a tofI mutant strain, suggesting that the two compounds functioned by different mechanisms and that the molecular target of J8-C8 was the TofI enzyme (119). Direct inhibition of TofI by J8-C8 was subsequently confirmed in vitro.…”
Section: Inhibition Of Ahl Productionmentioning
confidence: 99%